Clinical Features and Treatment Outcomes of Pulmonary Mycobacterium avium-intracellulare Complex With and Without Coinfections. (26th July 2022) - Wang, Grace; Stapleton, Jack T; Baker, Arthur W; Rouphael, Nadine; Creech, C Buddy; El Sahly, Hana M; Stout, Jason E; Jackson, Lisa; Charbek, Edward; Leyva, Francisco J; Tomashek, Kay M; Tibbals, Melinda; et al.
Abstract : Coinfections are more common in patients with cystic fibrosis and bronchiectasis. Infiltrates on imaging studies are seen more commonly in patients with coinfections, but coinfections did not affect treatment outcomes of pulmonary Mycobacterium avium complex.